MENCEGAH DAMPAK GLOBAL WARMING DENGAN PENDIDIKAN LINGKUNGAN BERBASIS ISLAMI - Sudarmanto, Agus (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2015)
Almost the entire population of the world feel increasingly hot temperatures , drought occurs everywhere. Uncertain seasons led to crop failure, especially among traditional farmers. It is said that according to experts, this condition is the impact of global warming.Every human activity to meet their needs certainly affect the environment. These conditions are known due to the increasing volume of the transportation needs of people at the same time the use of fuel such as gasoline, diesel, and others, the need for clothing and others have led to the emergence of new industries that the majority do not pay attention to the disposal of waste processed, the cutting and burning of forests and so in addition to the number of births in the world that is not balanced by the number of mortality.16To reduce the impact caused by global warming, the need for a new education and among the most important in the present and in the future, namely the Islamic -based environmental education . Education is related to the environment around human knowledge in accordance with the teachings of Islam, namely the Qur'an and hadith and maintain the various elements that can bring the threat of destruction, pollution or destruction.